Transitive and Strongly Transitive Neutrosophic Fuzzy Matrices - M. Anandhkumar; A. Savitha Mary; M. Kavitha; S. Subramanian; V. Sathishkumar; S.M. Chithra (Neutrosophic Sets and Systems)
This paper explores several fundamental properties of transitive Neutrosophic fuzzy matrices (TNFM) . It demonstrates that any Neutrosophic fuzzy matrices (NFM) can be expressed as the sum of a nilpotent Neutrosophic fuzzy matrices (NNFM) and a symmetric Neutrosophic fuzzy matrices (SNFM). Additionally, the concept of a strongly TNFM is introduced. Lastly, the canonical forms of both TNFM and strongly TNFM are presented.